26th IEEE International Conference on Distributed Computing Systems (ICDCS'06)
DOI: 10.1109/icdcs.2006.72
|View full text |Cite
|
Sign up to set email alerts
|

Routing in Networks with Low Doubling Dimension

Abstract: This paper studies compact routing schemes for networks with low doubling dimension. Two variants are explored, name-independent routing and labelled routing. The key results obtained for this model are the following. First, we provide the first name-independent solution. Specifically, we achieve constant stretch and polylogarithmic storage. Second, we obtain the first truly scale-free solutions, namely, the network's aspect ratio is not a factor in the stretch. Scale-free schemes are given for three problem m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 13 publications
1
101
0
Order By: Relevance
“…For planar graphs, a shortest path routing labeling scheme which uses 8n + o(n) bits per vertex is developed in [22], and a multiplicative (1 + )-stretched routing labeling scheme for every > 0 which uses O( −1 log 3 n) bits per vertex is developed in [39]. Routing in graphs with doubling dimension α has been considered in [1,10,37,38]. It was shown that any graph with doubling dimension α admits a multiplicative (1 + )-stretched routing labeling scheme with labels of size −O(α) log 2 n bits.…”
Section: Some Known Strategiesmentioning
confidence: 99%
“…For planar graphs, a shortest path routing labeling scheme which uses 8n + o(n) bits per vertex is developed in [22], and a multiplicative (1 + )-stretched routing labeling scheme for every > 0 which uses O( −1 log 3 n) bits per vertex is developed in [39]. Routing in graphs with doubling dimension α has been considered in [1,10,37,38]. It was shown that any graph with doubling dimension α admits a multiplicative (1 + )-stretched routing labeling scheme with labels of size −O(α) log 2 n bits.…”
Section: Some Known Strategiesmentioning
confidence: 99%
“…There are two popular models in the literature, the labeled routing model (in which naming and routing schemes are jointly considered) [9,10,27] and name-independent routing (in which node IDs are independent of the routing schemes) [2,16]. Generally speaking, the theoretical results in compact routing in a graph whose shortest path metric has a constant doubling dimension are able to obtain, with polylogarithmic routing table size, 1 + ε stretch routing in the labeled routing scheme (see [8] and many others in the reference therein), and constant stretch factor routing in the name-independent routing scheme [16,1] (getting a stretch factor of 3 − ε will require linear routing table size [1]). The schemes here are all by centralized constructions and aim to get the best asymptotic bounds.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that for some applications replacing distances by ranks can be meaningful. In particular, it is interesting to consider linear arrangement problem [18], closest pairs [24], distance labelling [66], shortest paths [3], detecting communities [61], and dimensionality reduction [15].…”
Section: Directions For Further Workmentioning
confidence: 99%